Analysis of Factors Affecting Original Local Government Revenue of East Java Province - Cundo Harimurti; Mohammad Sofyan (Budapest International Research and Critics University, 2022)
This study aims to analyze the factors that influence the original local government revenue of the province of East Java, namely: Population, gross regional domestic product, and inflation from 2015 to 2021. With multiple linear regression analyses, it is known that the Population has no significant negative effect on original local government revenue. Meanwhile, gross regional domestic product and inflation have a significant positive effect on original local government revenue.